Outcomes of Liver Transplantation Alone After Listing for Simultaneous Kidney. Issue 4 (April 2015) - Hmoud, Bashar; Kuo, Yong-Fang; Wiesner, Russell H.; Singal, Ashwani K.
<x xml:space="preserve">Abstract</x> Background Data on patient and liver graft survival comparing liver transplantation alone after listing for kidney with simultaneous liver kidney (SLK) transplantation are scanty. Methods United Network Organ Sharing network database (1994–2011) queried for liver transplantation alone after being listed for kidney and SLK transplants. Results Of 65, 206 first liver transplants, 3549 were listed for simultaneous kidney. Of these, 422 (12%) received only liver (LIST) and differed from SLK recipients for the white race (64% vs. 57%; 0.005), diabetes (27% vs. 37%; P = 0.02), model for end-stage liver disease era (68% vs. 82%; P = 0.0001), serum creatinine (2.9±1.9 vs. 4.3±2.5; P < 0.0001), dialysis (35% vs. 64%; P < 0.0001), and donor risk index (1.6±0.4 vs. 1.5±0.3; P < 0.0001). Overall survival was poorer in the LIST group (55% vs. 76%; P < 0.0001). A higher proportion of patients died within 2 days of transplantation in LIST group (11% vs. 0.5%; P < 0.0001), mostly from cardiovascular causes. After excluding these patients, odds of patient mortality and liver graft loss were about 1.2-fold and twofold higher in the LIST group. A total of 103 (24%) patients needed a renal transplantation in the LIST group with 16 (4%) receiving kidney within first year after transplantation. After excluding patients receiving kidney within first year, about 33% recovered renal function to above estimated GFR of greater than 60 mL per min. Conclusion Guidelines are needed for patient selection to list for and receipt of simultaneous liver kidney transplantation.